The Complex Of Environmental Ideas In The Prose Of The 1920s-1930s And Methods Of Its Artistic Presentation - Viktorovna Gurlenova, Ludmila; Alexandrovna Sidorova, Tatyana; Evgenievna Kotsova, Elena; Yurievna Elepova, Marina; Nikolaevna Ivanishcheva, Olga (Opción, 2019)
The article is relevant since it studies such an important function of the literature of the first third of the 20th century as its active discussion of fun- damental issues, including the role of nature in the Earth development, the attitude of people towards it and ways of raising environmental awareness. The article aims to explore environmental ideas of S. Klychkov’s and L. Leonov’s prose depicting a folk lifestyle in the context of natural environ- ment and folk culture preserving mythological views on nature, as well as to reveal the artistic implementation of their environmental concepts. The ar- ticle states that these writers were opponents of the mechanistic worldview (the philosophical basis of technocracy rapidly developing in science and culture); they presented nature as a living organism that can function only as an entity. This idea was considered from different perspectives and was represented as a complex of interrelated aspects. Environmental ideas in the artistic world of S. Klychkov’s and L. Leonov’s works were expressed in ac- cordance with the depicted layer of national life and culture. The key to their understanding is ideas about the world contained in etiological, cosmogonic and eschatological myths. Based on these ideas, both writers create their own myth about the struc- ture of nature: its inner organization, natural objects, phenomena and forc- es. They created the artistic world of their works with the logic of scientif- ic knowledge in order to systematize ideas and mythological projections, restore mythological thinking based on archetypal images, motives and principles of creating the mythological-poetic worldview. Environmental ideas include such aspects as philosophical, aesthetic and ethical, i.e. they are the result of the writers’ comprehensive understanding of nature and the person’s attitude towards it.